Further results on super edge-magic graphs - Afzal H.U.; Ather M.; Baig A.Q.; Maheshwari A. (Utilitas Mathematica, 2019)
We present here two special classes of graphs namely pyramidion ladder and Cn-book and analyze their super edge-magicness, we further exhibit a few results to form new super edge-magic graphs from the old ones. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.